Inhibition of Listeria monocytogenes by the Staphylococcus capitis - derived bacteriocin capidermicin. (April 2021) - Lynch, David; Hill, Colin; Field, Des; Begley, Máire
Abstract: Natural methods to control food pathogens are required and bacteriocins have received much interest in this regard. The aim of this study was to investigate the ability of the novel bacteriocin capidermicin to inhibit Listeria monocytogenes. Agar-based deferred antagonism assays were carried out with the capidermicin producer against 17 L. monocytogenes strains and large zones of inhibition were observed for 12 strains. Minimal inhibitory concentration assays performed with purified capidermicin peptide revealed MIC values between 680 nM and 11 μM. Biofilm assays were performed with five L. monocytogenes strains. Addition of capidermicin prevented biofilm formation by one strain and could remove pre-established biofilms of all five strains. Broth based growth experiments demonstrated that addition of capidermicin resulted in an extended lag phase of both L. monocytogenes strains tested. Kill-curve experiments showed that capidermicin was able to potentiate the anti- Listeria effects of the lantibiotic nisin. This enhanced killing by the combination of both peptides was also observed in model food systems (cottage cheese and chocolate milk). In summary, we show that capidermicin can inhibit L. monocytogenes and warrants further investigation as a potential natural agent for the control of this pathogen. Highlights: Capidermicin exhibited anti-listerial activity in the nano- and micromolar range. Capidermicin reduced pre-established L. monocytogenes biofilms. Addition of capidermicin enhanced the anti-listerial activity of nisin in broth. Addition of capidermicin enhanced the activity of nisin in model food systems.